2018
DOI: 10.1287/mnsc.2017.2800
|View full text |Cite
|
Sign up to set email alerts
|

I Lie? We Lie! Why? Experimental Evidence on a Dishonesty Shift in Groups

Abstract: Unethical behavior such as dishonesty, cheating and corruption occurs frequently in organizations or groups.Recent experimental evidence suggests that there is a stronger inclination to behave immorally in groups than individually. We ask if this is the case, and if so, why. Using a parsimonious laboratory setup, we study how individual behavior changes when deciding as a group member. We observe a strong dishonesty shift. This shift is mainly driven by communication within groups and turns out to be independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
182
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(195 citation statements)
references
References 32 publications
12
182
0
1
Order By: Relevance
“…1 This is shown in the lab (e.g., Erat and Gneezy, 2012;Houser et al, 2012;Conrads et al, 2014;Kocher et al, 2016) 2 and in the field (Azar et al, 2013;Bucciol et al, 2013). Although, the literature predominately finds that men cheat significantly more, some studies find no gender differences (e.g., Childs, 2012;Djawadi and Fahr, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…1 This is shown in the lab (e.g., Erat and Gneezy, 2012;Houser et al, 2012;Conrads et al, 2014;Kocher et al, 2016) 2 and in the field (Azar et al, 2013;Bucciol et al, 2013). Although, the literature predominately finds that men cheat significantly more, some studies find no gender differences (e.g., Childs, 2012;Djawadi and Fahr, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…This enhances the classical theory on immoral behavior as a product 20 of income effects and the probability of getting caught and punished (Fischbacher & Föllmi-21 Heusi, 2013;Gneezy, 2005). Further research found that the intrinsic costs of lying depend on 22 the context: Kocher, Schudy, and Spantig (2018) reported that teams lie more often than indi-23 viduals. This effect is driven by communication which seems to reduce moral costs regarding 24 dishonesty.…”
Section: And Thementioning
confidence: 57%
“…The general design was based on the die-rolling task introduced by Kocher et al (2018) which 125 is an extension of the Fischbacher and Föllmi-Heusi (2013) task. Before the task was carried 126 out, participants had to correctly answer control questions regarding the task to ensure their 127 understanding (see appendix A.1).…”
Section: Die-rolling Task 124mentioning
confidence: 99%
See 1 more Smart Citation
“…Closely related to our study are those of: Conrads, Irlenbusch, Rilke, and Walkowitz (2014) who found that people lie more when the returns to lying must be shared with another; Alempaki, Doğan and Saccardo (2016) who found that senders in a sender-receiver game lie less when the receivers played fairly in a prior dictator game; Weisel and Shalvi (2015) who found that, in a sequential twoplayer game in which both must lie for each to secure a positive monetary payoff, when the first player lies, the second player reciprocates by also lying; and Kocher, Schudy, and Spantig (2016) who found that communication within a group increases dishonesty. However, none of these prior studies investigate simultaneous coordination involving immoral behavior or isolate the effect of having a potential accomplice from other pro-social motivations for lying, while at the same time eliminating all possible forms of communication, including signaling intent through choice of action.…”
Section: Introductionmentioning
confidence: 99%